Satisfacción familiar, estado afectivo y consumo problemático de alcohol en jóvenes universitarios de Lima Metropolitana - Oneto Crovetto, Constanza (2019)
The objective of this study is to establish the relationship between family satisfaction, positive affective status, negative affective status and the problematic alcohol consumption in young people aged between 18 to 24 from private universities in Lima Metropolitana. This is because there is evidence showing that consumption of alcoholic beverages in adolescents can be caused by family dynamics, as this is the core of our society and is considered a reference for the members that make it up (Jiménez, 2012). There were 193 participants evaluated with the previously mentioned instruments (M= 20.72, SD= 1.71, 34.2% of women). The results indicated the presence of statistically significant correlations between certain variables. Specifically, between family satisfaction and positive affect (r= 0.24) and between family satisfaction and negative affect (r= -0.32). The instruments presented evidence of reliability. The family satisfaction instrument (ESFA) 0.95, the positive and negative affect scale (PANAS), obtained a reliability of 0.88 and the disorders due to alcohol identification (AUDIT ) 0.78. This research could be applied in clinical settings for future research. Within the limitations must be mention that the investigation has a non – probabilistic sampling, wich results in a limited ability to generalize the results.